1997
DOI: 10.1021/ci9601168
|View full text |Cite
|
Sign up to set email alerts
|

A QSAR Study of the Antimalarial Activity of Some Synthetic 1,2,4-Trioxanes

Abstract: The antimalarial activity of a series of synthetic 1,2,4-trioxanes is correlated with molecular structure by using a pharmacophore search method (CATALYST). The technique is shown to have predictive accuracy and confirms that docking between an active trioxane and the receptor, heme, is the crucial step for drug action.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

1997
1997
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 16 publications
1
38
0
1
Order By: Relevance
“…In contrast an inactive analogue of artemisinin, deoxyartemisinin, docks in a different manner (51,52). Similar studies with synthetic endoperoxides suggest that docking between an active trioxane and the receptor, heme, is the crucial step for the drug action (53,54). In these studies, peroxide bond of the trioxane is found to lie close to the central iron atom of heme, suggesting it to be an important criterion for parasiticidal action.…”
Section: Discussionmentioning
confidence: 76%
“…In contrast an inactive analogue of artemisinin, deoxyartemisinin, docks in a different manner (51,52). Similar studies with synthetic endoperoxides suggest that docking between an active trioxane and the receptor, heme, is the crucial step for the drug action (53,54). In these studies, peroxide bond of the trioxane is found to lie close to the central iron atom of heme, suggesting it to be an important criterion for parasiticidal action.…”
Section: Discussionmentioning
confidence: 76%
“…Caso a estrutura do complexo receptor-fármaco seja conhecida, as interações entre ambos podem ser investigadas com mais detalhes. Estudos computacionais e quantitativos que correlacionam a estrutura química e a atividade biológica de uma série de fármacos e análogos têm apontado para os mecanismos de ação e têm dado diretrizes para a síntese de novos derivados mais eficientes [11][12][13][14][15][16][17] . No caso específico do tratamento da malária com artemisinina, há evidências experimentais de que o mecanismo de ação do fármaco envolve a formação de um complexo de transição heme-artemisinina.…”
Section: Figura 1 Estrutura Do Hemeunclassified
“…Structures of the 4-quiniolinecarbinolamines were imported into CATALYST to create a training set, and energy was minimized to the closest local minimum with the generalized CHARMM-like force field as imple- considering each compound as an ensemble of conformers representing different accessible areas in 3D space. The "best searching procedure" was applied to select representative conformers within 10 kcal/mol of the global minimum (12). CATALYST allows the use of structure and activity data for a set of lead compounds to create a hypothesis characterizing the activity of the lead set.…”
Section: Mefloquine Analogsmentioning
confidence: 99%